The Effect of Commitment and Organizational Culture on Employee Performance Through Organizational Citizenship Behavior as an Intervening Variable - Irwan; Inah Mutmainna; Parman; Rusmin Nuryadin; Akhsan; Rudi Arafah (www.amertainstitute.com, 2025)
This study aims to determine and analyze the effect of Commitment and Organizational Culture on Employee Performance through Organizational Citizenship Behavior as an intervening variable at the Public Works and Spatial Planning Department of Parepare. This research uses a quantitative method approach with a sample is 71 employees. Research data analysis is processed using the Smart PLS analysis. The data collection methods used were questionnaires, observation, and documentation. The results obtained in the study are as follows: Organizational commitment has a positive and significant effect on employee performance; organizational culture has a positive and significant effect on employee performance; organizational citizenship behavior has a positive and significant effect on employee performance; organizational culture has a positive and significant effect on employee performance through organizational citizenship behavior; and organizational commitment does not have a significant effect on employee performance through organizational citizenship behavior among employees of the Department of Public Works and Spatial Planning in Parepare City. Therefore suggested that to enhance employee performance, the Department of Public Works and Spatial Planning in Parepare City should prioritize strengthening organizational culture, commitment, and organizational citizenship behavior (OCB). A strong culture and high OCB directly improve performance, with culture also influencing performance indirectly through OCB. This indicates that fostering shared values and encouraging voluntary, proactive behavior among employees are essential strategies. However, the lack of a significant indirect effect of organizational commitment through OCB implies that commitment alone is not enough to drive extra-role behavior. Therefore, management must implement programs that not only build commitment but also translate it into meaningful actions. Enhancing communication, recognition, and leadership support can further stimulate OCB and improve overall performance. These findings highlight the importance of aligning organizational values and behaviors to achieve optimal employee outcomes.